Proposed mechanisms of action participating in the hypoglycemic effect of the traditionally used Croton guatemalensis Lotsy and junceic acid, its main compound - Angelina Daniela Moreno-Vargas; Angelina Daniela Moreno-Vargas; Adolfo Andrade-Cetto; Fernanda Artemisa Espinoza-Hernández; Gerardo Mata-Torres (Frontiers Media S.A., 2024)
Croton guatemalensis Lotsy (Euphorbiaceae) is an important traditional medicine that is used by the Cakchiquels of Guatemala to control hyperglycemia in patients with type 2 diabetes. Previous studies have shown that administration of this plant induces an acute hypoglycemic effect during fasting and that the main compound is junceic acid, a diterpenoid with a clerodane skeleton; however, junceic acid has not been reported to have hypoglycemic activity in the literature. As the mechanisms involved in the hypoglycemic effect of C. guatemalensis remain unknown, the objective of the present investigation was to elucidate the hypoglycemic mechanisms of this species, as well as its major compound, junceic acid. The results indicated that, similar to complete extract, junceic acid exhibited a hypoglycemic effect in hyperglycemic rats. Both C. guatemalensis extract and junceic acid inhibited the activity of two rate-limiting enzymes involved in hepatic glucose production; however, compared with chlorogenic acid, junceic acid had a more potent effect on glucose-6-phosphatase levels than chlorogenic acid, which was used as a positive control. Furthermore, both fasting and postprandial insulin levels decreased in healthy and hyperglycemic rats despite reduced blood glucose levels in both metabolic states, suggesting a potential insulin-sensitizing effect. However, neither of these compounds potentiated the effect of insulin in insulin tolerance tests nor inhibited the enzyme activity of protein tyrosine phosphatase 1B, a negative regulator of the insulin pathway. Therefore, the insulin-sensitizing effect is thought to be independent of insulin and mediated by potential activation of the AMP-activated protein kinase pathway. The specific activation of this master regulator in β-cells results in the inhibition of insulin secretion in a healthy state and the restoration of the insulin response under conditions of glucotoxicity; these effects were observed after the administration of the extract and junceic acid in healthy and hyperglycemic rats. Overall, the main findings of this study establish a basis of the mechanisms of action of C. guatemalensis and its main compound, junceic acid, in terms of their hypoglycemic effect.